Pengaruh Pemberian Ekstrak Buah Belimbing Wuluh (Averrhoa Bilimbi) Sebagai Suplemen Dalam Pakan Buatan Untuk Meningkatkan Pertumbuhan Dan Kelangsungan Hidup Benih Ikan Nila Gift (Oreochromis Niloticus) - Sefrianto, Ade; Hamron, Novita; Warman, Indra; Oktamalia, Oktamalia; Andriyeni, Andriyeni (Perkumpulan Dosen Muda (PDM) Bengkulu, 2023)
Gift tilapia is a fish that is widely favoured by people in Bengkulu province and includes fish that has important economic value. Efforts to increase the growth rate of gift tilapia is one idea to increase production. As an important source of protein for the community. Gift tilapia has the advantage of being easy to breed, fast growth rate, and can be cultivated intensively and extensively with high density. The survival rate of tilapia seeds is highly influenced by several factors of the aquatic environment such as temperature, pH and feed. The growth of tilapia seeds also depends on the quality of the feed given every day, the higher the nutritional value of the feed given, the growth rate will increase, so therefore the provision of belimbing wuluh juice is expected to help improve the growth system and resilience of gifted tilapia seeds. This research was conducted in April to May located in the yard of the orange alley house, in Karang Anyar II Village, Argamakmur District, North Bengkulu. This study used a completely randomised design with 4 treatments and 3 replicates, namely Treatment A (no extract 0 ml/kg pellets), B (star fruit extract 55 ml/kg pellets), C (star fruit extract 75 ml/kg pellets) and Treatment D (star fruit extract 95 ml/kg pellets). The results showed that the provision of star fruit extract in artificial feed had a very significant effect on the length growth of gift tilapia, and the weight growth of gift tilapia. The best survival of gift tilapia in treatment C (star fruit extract 75 ml/kg pellets) with a survival value of 100% and produced the highest length growth in treatment D of 15.12 cm and the highest absolute weight growth was in treatment D with a value of 16.6 grams.